'Learning to Hold a Paradox': A Narrative Review of How Ambiguous Loss and Disenfranchised Grief Affects Children in Care. Issue 5 (11th November 2022) - Leitch, Jude
Abstract : Separation and loss characterise a child's experience in care, yet losses in the care-experienced population have rarely been studied as a possible source of trauma or as events that may justify a grief response. A literature search of five databases yielded 592 publications. 41 full text articles were reviewed, 16 publications were included. Thematic analysis revealed: children in care are affected by two broad type of ambiguous loss, relationship losses and psychosocial losses; behaviours labelled as 'problem' behaviours may in fact be indicators of the manifestations of ambiguous loss and disenfranchised grief; manifold ambiguous losses associated with multiple placement moves has a cumulative effect that can generate long-term negative consequences; the effects of ambiguous loss can be offset by supporting children in care to understand that their losses may not be resolvable, to build tolerance to this ambiguity, to rebuild their identity through forging permanent connections, and to make meaning of their situations. Social workers have a key role in supporting those in care to understand, process and cope with their ambiguous losses but diminishing the burden of loss must also be a systemic focus if meaningful change is to be realised for this community of vulnerable young people.